Argumentos embasadores do processo de alienação parental no Estado do Paraná - Munhoz, Rossana Nadolny (2017)
The general objective of this work it is in raising arguments that published court decisions in cases of Parental alienation in the State of Paraná defining and establishing the distinctions between Parental Alienation and Parental Alienation syndrome and as specific objectives: identify by means of judgments obtained from the website of the Court of the State of Paraná as being understanding about Parental alienation, the arguments by alienating and alienated posts and the reasons of the judges in the cases; analyze if the courts decisions based on technical reports and what consequences arising from psychological reports and compare the legal understanding (12.318 Law/10) and the forensic psychology concerning Parental Alienation and Parental Alienation Syndrome and psychological abuse and compare the legal understanding (Law 12.318 / 10) and forensic psychology concerning Parental Alienation and Parental Alienation Syndrome and Psychological Abuse. The methodology used quantitative nature, qualitative research, bibliographic and documentary, as well as the use of relevant legislation, through which will be investigated on the Parental Alienation through the analysis of court cases, seeking elements that published decisions in the courts. Justified the choice of the theme given to your relevance, by the endless bickering in the judiciary, in which children and adolescents are involved in discord and often used as tools of revenge between couples in dispute.